Tree diversity and biomass carbon stock analysis along altitudinal gradients in coffee-based agroforestry system of Western Ethiopia - Chemeda, Beshea Abdissa; Wakjira, Feyera Senbeta; Hizikias, Emiru Birhane (Informa UK Limited, 2022)
Agroforestry systems are thought to reconcile biodiversity protection with food production and as a means of climate change adaptation and mitigation options. The contribution of a coffee-based agroforestry system to tree diversity and carbon stock along altitudinal gradients in Western Ethiopia was assessed. At 500-m intervals, six transect lines were methodically set up throughout the altitudinal gradient. There were made a total of 60 sample plots, each measuring 40 m by 40 m. A total of 34 woody species were identified. Biomass carbon stocks and tree diversity were quantified across altitudinal gradients. In the middle altitude, there were more woody species (28) than in the top altitude, where there were only a few species (16). The tree plants stored around 40.6 t ha−1 of biomass carbon on average. Aboveground biomass had a carbon stock of 32.22 C t ha−1, whereas belowground biomass had a carbon stock of 8.38 C t ha−1. The lower altitude biomass carbon stocks were substantially bigger than the upper altitude, which were 48.4 C t ha−1 and 25.67 C t ha−1, respectively. With increasing altitude, the study found a statistically significant negative link between tree diversity and biomass carbon storage (P < 0.05). The negative link between biomass carbon stock and altitude was that tree parameters that determine the amount of biomass carbon sequestered in a plant, such as basal area, tree diversity, and density, decreased as altitude increased. Despite differences along altitudinal gradients, the systems supported a diverse range of tree species and biomass carbon stocks.